Organizing logic multiplicity in hybrid organizations: The role of organizational culture - Alexander Pinz; Benedikt Englert; Bernd Helmig (Nonprofit Management and Leadership, 2024)
Abstract Hybrid organizations must deal with institutional complexity and find ways to manage conflicting demands in their organizational environment to engage in their required, day-to-day activities. The objective of this qualitative research is to elaborate on the mechanisms that hybrid organizations use to mitigate the destabilizing effects of such institutional logic multiplicity in their value creation processes. By combining value configuration analyses and the hybrid organizing concept as a theoretical background, the authors conduct a case study with 14 nonprofit microfinance organizations (MFOs) that illustrates the importance of an integrative organizational culture as a core foundation that can align and integrate social and economic demands. Successful nonprofit MFOs align competing institutional logics in a hierarchy of goals, explicitly defining their means and objectives. Independent of the type of logic multiplicity they face, they use the hierarchy to define their organizational identity and transfer it to a corresponding organizational culture that can balance diverse institutional demands. From a theoretical perspective, this study advances institutional logic approaches; it also identifies effective mechanisms hybrid organizations can use to cope with logic multiplicity by applying a value configuration perspective.
Keywords: 330; hybridity; microfinance; nonprofit organizations; organizational culture